Corticospinal Facilitation During Hand Laterality Judgments? - Ferron, Lucas (Université d'Ottawa / University of Ottawa, 2017)
Observing others performing actions is a common way to learn new motor skills. Such ability appears to be linked with one’s ability to imagine actions (motor imagery) (Wang et al. 2014). While motor imagery has been widely used in the context of athletic performance, the same approach has also been advocated in rehabilitation settings, where they often target populations with chronic pain using mobile health applications (de la Vega and Miro 2014). However, we still have very limited information as to how the ability to perform motor imagery addresses this rehabilitation application (Johnson et al. 2012). In the present study, we examined this question by looking at modulation in corticospinal excitability in the context of a motor imagery task. The imagery task itself consisted of judging whether images depicting hands in different postures represented either right or left hands. Based on prior neuroimaging and chronometric studies, such laterality judgments about hand postures are thought to involve mental rotations of one’s own hand (i.e., a form of implicit motor imagery) and thus provided an ideal context to evaluate if advocating such strategy is a valid approach to elicit motor activation in rehabilitation patients (Butson et al. 2014; Goble and Brown 2008; Parsons 1987). To this end, we used non-invasive transcranial magnetic stimulation (TMS) to probe the excitability of the motor system while young healthy participants performed mental rotations in the hand judgment task. Corticospinal excitability was tested in both hemispheres separately (target muscle: first dorsal interosseous) with participants (n=18) seated in front of a computer screen while they performed hand laterality judgments using a commercial set of pictures depicting bare hands in different postures. Excitability was tested also under two other conditions to contrast with variations measured during the hand laterality task, i.e. a mental counting task and a control task (looking at the image of a static foot). In all conditions, TMS (110% resting motor threshold) was set to trigger at ~half of the mean response time in the hand laterality task measured prior to testing with TMS. Comparison of task-related variations in MEP amplitude revealed no significant hemispheric main effect or interaction, although MEPs tended to be larger in general in response to left TMS. A “task condition” effect was observed owing to the large MEP facilitation elicited during the mental counting task, which was significantly different (p<0.001) from either the control “Foot” task or the hand rotation task. In fact, the latter task tended to be associated with MEP depression. A secondary experiment involving a subset of participants (n=6) to examine the influence of image contents (i.e. hand performing actions instead of bare hands) and probing more proximal muscles produced similar results as the main experiment. These results indicate that the general assumption that laterality tasks involving body parts will lead to internal mental rotation and motor activation and enhanced excitability is not necessarily true. In fact, our observations suggest that participants may rely on non-motor strategies based on visual cues when making laterality judgments about body parts. As well, no evidence for hemispheric asymmetry was found with the hand laterality task which is in line with other recent reports. Collectively, these results highlight the need to exert caution when using laterality tasks for rehabilitation purposes. One cannot simply assume that such tasks will translate into motor simulation and facilitation of the motor system. More research should be undertaken before recommending the hand mental rotation task as a viable rehabilitation option for chronic pain.
Keywords: Transcranial Magnetic Stimulation; Motor evoked potentials; Motor imagery; Mental rotation; Laterality task